Peculiarities of manufacture of castings of diesel engines pistons out of secondary alloys - E. I. Marukovich; A. A. Andrushevich; I. N. Kazanevskaya; M. N. Churik (Литьë и металлургия)
The article considers peculiarities of production technology of high-quality castings of diesel engines pistons out of secondary alloys.